The Response of War Trauma A comparative study between Half Of A Yellow Sun by the Nigerianwriter"ChymemandaNegozieAdichie"and"YaMarim" by the Iraqi writer "Sinan Antoon". - محمود, عيد حسن; حسن, طلال محمّد; عبد الرحمن, محمّد سليم (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aims to analyze war trauma in perspective of comparative cultural criticism at two different cultural contexts : the Middle Eastern "Iraq" and the post-colonial "Nigeria" questioning two cultural- psychological phases in criticizing the traumatized characters: acting- out and making-through via linking the psychological concepts to the cultural and social position of the characters. The conscious of the characters at the acting-out phase counters by defenses mechanisms like the dark swoops which reflect political and social concerns. On contrary, making-through phase reveals that the characters try to live out of the crisis-self by communicating to society and forgetting its own trauma narrative through developing dialogism strategies free the narrative plot from the subjectivity, helping to exceed the painful past and transform it into anti-power to be baptized. To conclude, the acting –out phase reveals the blackmailing of war to the unconscious of the characters which portrays their conscious melancholia centers ,at where they see the world as a delusions- pathway. while, making-through phase in both communication and adaptation aspects reveals the transcendence of trauma pain imposed upon the scrimmage of the sieged self-story in acting-out phase to be finished to the internal negotiations with the external world which accept the changeability position of the victim.